Spatial and temporal analysis of drought-related climate indices for Hungary for 1971–2100 - Anna Kis; Péter Szabó; Rita Pongrácz (Hungarian Geographical Bulletin, 2023)
The lack of precipitation may cause severe damage in different sectors, especially in agriculture and forestry, therefore, its analysis is a key element of adaptation strategies in the changing climate. In the present study, we selected different climate indices as important indicators for forests to investigate the current and future wet and dry conditions in summer in Hungary. For the historical period (from 1971), the observation-based HuClim dataset is used, which already shows a slight drying trend in the past 50 years, especially in June. For the future, regional climate model simulations from the EURO-CORDEX program are used, taking into account two different RCP scenarios (a business-as-usual scenario and an intermediate mitigation scenario, i.e., RCP8.5 and RCP4.5, respectively). Since mitigation starts to affect the climate system after about 20 years, results do not differ substantially for the two scenarios until 2060, however, the simulated changes highly depend on the applied RCP scenario in the late 21st century. Based on the De Martonne Index, a large expansion of semi-arid conditions is projected for the future in July and even more in August. The analysis of the Forestry Aridity Index shows that the steppe category will become dominant in 2081–2100, while the category optimal for beech may disappear entirely from Hungary according to the RCP8.5 scenario.